2009
DOI: 10.1161/hypertensionaha.109.136069
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Sympathetic Nervous System in Schlager Genetically Hypertensive Mice

Abstract: Early studies indicate that the hypertension observed in the Schlager inbred mouse strain may be attributed to a neurogenic mechanism. In this study, we examined the contribution of the sympathetic nervous system in maintaining hypertension in the BPH/2J mouse and used c-Fos immunohistochemistry to elucidate whether neuronal activation in specific brain regions was associated with waking blood pressure. Male hypertensive (BPH/2J; n=14), normotensive (BPN/3J; n=18), and C57/Bl6 (n=5) mice were implanted with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 28 publications
8
91
1
Order By: Relevance
“…9 These findings not only suggest that the hypertension observed is likely due to an overactive SNS, the pattern of night-time arousal activation is highly suggestive of the pattern associated with stress similar to that observed in human early morning BP surge. 3 Thus, we hypothesize that Schlager BPH/2J mice may respond considerably more in terms of BP rise than BPN/3J mice to a stressful stimulus.…”
Section: Original Contributionssupporting
confidence: 64%
See 1 more Smart Citation
“…9 These findings not only suggest that the hypertension observed is likely due to an overactive SNS, the pattern of night-time arousal activation is highly suggestive of the pattern associated with stress similar to that observed in human early morning BP surge. 3 Thus, we hypothesize that Schlager BPH/2J mice may respond considerably more in terms of BP rise than BPN/3J mice to a stressful stimulus.…”
Section: Original Contributionssupporting
confidence: 64%
“…The very high levels of BP in BPH/2J mice are most evident during the active period, but the arousal associated with nocturnal behavior would not typically be considered "aversive. " We have previously shown that the hypertension is directly correlated to the activity of the MeAm, 9 and this region is known to integrate the emotional response to stress. 17 It is known to be necessary for the manifestation of the pressor response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…BPH/2J mice are a model of lifelong hypertension on a genetic basis and manifest some of the cardinal features of essential hypertension, i.e., neurohumoral dysfunction, sympathetic activation, cardiac hypertrophy, and kidney atrophy (58,59). Due to long-lasting hypertension, BPH/2J mice are valuable in hypertension research, akin to spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that there is a greater sympathetic contribution to the hypertension in BPH/2J mice. The use of radiotelemetry devices recording for 24 h identified that BPH/2J mice not only display hypertension but also have a greater day-night difference in BP compared with BPN/3J mice [3]. Interestingly, the greater BP surge in BPH/2J mice was associated with activation of neurons in the amygdala and hypothalamus indicating brain regions important for cardiovascular regulation of stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…The use of radiotelemetry devices recording for 24 h identified that BPH/2J mice not only display hypertension but also have a greater day-night difference in BP compared with BPN/3J mice [3]. Interestingly, the greater BP surge in BPH/2J mice was associated with activation of neurons in the amygdala and hypothalamus indicating brain regions important for cardiovascular regulation of stress [3]. Indeed, BPH/2J mice also respond markedly more than BPN/3J mice to aversive stress demonstrated by 70-90% greater pressor responses and only small effects (þ20%) induced by non-aversive stress such as feeding indicating typical levels of arousal [4].…”
Section: Introductionmentioning
confidence: 99%